Characterization, Recombinant Production, and Bioactivity of a Novel Immunomodulatory Protein from Hypsizygus marmoreus - Shuhui Yu; Ying Wang; Yingying Wu; Dapeng Bao; Wei Bing; Yan Li; Hongyu Chen (Molecules, 2023)
A novel fungal immunomodulatory protein (FIP), identified as FIP-hma, was discovered in the genome of an edible mushroom Hypsizygus marmoreus. Bioinformatics analysis suggested FIP-hma contained the cerato-platanin (CP) conserved domain and was categorized into Cerato-type FIP. In phylogenetic analysis, FIP-hma was clustered into a new branch of the FIP family, displaying large system divergence from most of the other FIPs. The higher gene expression of FIP-hma was observed during the vegetative growth stages than that during the reproductive growth stages. In addition, the cDNA sequence of FIP-hma was cloned and successfully expressed in Escherichia coli (E. coli) BL21(DE3). The recombinant protein of FIP-hma (rFIP-hma) was neatly purified and isolated by Ni-NTA and SUMO-Protease. The iNOS, IL-6, IL-1β, and TNF-α levels of RAW 264.7 macrophages were upregulated by rFIP-hma, indicating its activation of an immune response by regulating central cytokines. No cytotoxic effects were observed in an MTT test. The findings of this work discovered a novel immunoregulatory protein from H. marmoreus, provided a systematic bioinformatic profile, suggested an effective approach for its heterologous recombinant production, and reported its potent immunoregulatory activity in macrophages. This study sheds light on the physiological function research of FIPs and their further industrial utilization.